Opciones de caminos para las obras de infraestructura del proyecto hidroelectrico de Brujo I. utilizando un sistema de informacion geográfica. - Orozco-Barrantes, Antonio (Instituto Tecnológico de Costa Rica, 2002)
The application of Geographical Information System (GIS) technology was evaluated for the design of country routes within the Río Savegre watershed. A cartography model was developed that includes four different variables: topography, climate, hydrology, and geology. As a result it was obtained a road that communicates five communities inside the watershed and the infrastructure of the Hydroelectric Project “Brujo I”. This road presents the inconvenience of passing through a large extension of primary forest. Taking into account the limits of the use of the soil and the irregularity of the topographic conditions of the study area, it was decided to dispose 50% of the 14 alternatives routes obtained. For the remaining seven options, six of them need to be developed trough the primary forest. Consequently, there are doubts about their construction. From the evaluation done it was concluded that the route communicating Providencia Town with the dam section is the one with the minor impact to the natural resources of the area.
Proyecto de Graduación (Bachillerato en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2002.
Keywords: Recursos naturales; Software; Datos; Precipitación; Bosques; Geología